Formation and removal of 1, N6-dimethyladenosine in mammalian transfer RNA. Issue 17 (12th September 2022) - You, Xue-Jiao; Zhang, Shan; Chen, Juan-Juan; Tang, Feng; He, Jingang; Wang, Jie; Qi, Chu-Bo; Feng, Yu-Qi; Yuan, Bi-Feng
Abstract: RNA molecules harbor diverse modifications that play important regulatory roles in a variety of biological processes. Over 150 modifications have been identified in RNA molecules. N 6 -methyladenosine (m 6 A) and 1-methyladenosine (m 1 A) are prevalent modifications occurring in various RNA species of mammals. Apart from the single methylation of adenosine (m 6 A and m 1 A), dual methylation modification occurring in the nucleobase of adenosine, such as N 6, N 6 -dimethyladenosine (m 6, 6 A), also has been reported to be present in RNA of mammals. Whether there are other forms of dual methylation modification occurring in the nucleobase of adenosine other than m 6, 6 A remains elusive. Here, we reported the existence of a novel adenosine dual methylation modification, i.e. 1, N 6 -dimethyladenosine (m 1, 6 A), in tRNAs of living organisms. We confirmed that m 1, 6 A is located at position 58 of tRNAs and is prevalent in mammalian cells and tissues. The measured level of m 1, 6 A ranged from 0.0049% to 0.047% in tRNAs. Furthermore, we demonstrated that TRMT6/61A could catalyze the formation of m 1, 6 A in tRNAs and m 1, 6 A could be demethylated by ALKBH3. Collectively, the discovery of m 1, 6 A expands the diversity of RNA modifications and may elicit a new tRNA modification-mediated gene regulation pathway. Graphical Abstract: